Cleistogamy and phylogenetic position of Viola uliginosa (Violaceae) re‐examined. (12th July 2016) - Małobęcki, Andrzej; Marcussen, Thomas; Bohdanowicz, Jerzy; Migdałek, Grzegorz; Słomka, Aneta; Kuta, Elżbieta
Abstract : Viola uliginosa is an endangered species throughout its range in Central Europe. Based on an unusual combination of morphological characters, including a reported lack of cleistogamous (CL) flowers, it was previously placed in the monotypic subsection Repentes, section Viola . Available individual phylogenetic analyses identify V. uliginosa as a lineage deeply embedded in section Viola, but hitherto its exact position was unknown. Here we confirm the occurrence of cleistogamy in V. uliginosa . Unlike other species of section Viola, V . uliginosa produced both chasmogamous and CL flowers at the same time, not at different times of the year (seasonal cleistogamy). The two flower types differed conspicuously in morphology and microstructure, especially in size and shape of the pistil and stamens as confirmed by scanning electron microscopy. Secondly, we resolved the phylogenetic position of V . uliginosa as a lineage deeply embedded in subsection Rostratae by means of a multigene multispecies coalescent analysis using *BEAST. In this analysis, V . mirabilis and V . uliginosa were successive sisters to the rest of subsection Rostratae and, because allopolyploids exist between V . mirabilis and the last one, subsection Rostratae needs to comprise all these taxa to be monophyletic. The evolution of key morphological traits is briefly discussed.